Jogo educativo: instrumento para retomada da discussão da saúde da mulher na gravidez, parto e nascimento. - Bezerra, Fabíola Gessika Coelho (2016)
The discussion on women's health in pregnancy, childbirth, and birth takes up broader reflections on access to educational practices in health services, where care is often confined to individual prenatal consultations. In the search for effective strategies we understand the need to make efforts to promote technologies of support and education to health. The study aimed to elaborate educational games aimed at the health of women with developments for interventions in pregnancy, childbirth and birth. It is an interventionist study based on action research, considering in the organization of the methodological course the phases suggested by Thiollent. To carry out this methodological process of research, we used the arch method, by Charles Maguerez. The study was developed between February and April 2016, in a Basic Health Unit of the municipality of Caucaia-Ceará. As an initial stage of data collection, a semi-structured interview was conducted with forty-four pregnant women, using an instrument that contemplates socioeconomic and obstetric aspects. Four workshops were then carried out to produce the educational game following the steps suggested in the Charles Maguerez arch method, where the information was collected using the press conference through the workshop technique. This research respects the ethical precepts, being approved by the Committee of Ethics in Research under nº 1.403.820. The results evidenced the preparation of four educational games focused on pregnancy, childbirth and birth. A board game was developed with the suggestion of the name of the pathways for childbirth, where information on feeding, guidelines on complaints, vaccination, differences between normal delivery and cesarean delivery and postpartum care were developed. It was proposed a memory game to expose about the care of the newborn, a domino to discuss about contraceptive methods and a puzzle about the correct handle of breastfeeding. Supported by the idea that with simpler technologies that approximate everyday life, educational processes with games become more attractive because they are a socially significant element, being present in the life of the community.